Saving the Wretched of the Earth - Betcher, Sharon V. (Disability Studies Quarterly, 2006)
In this essay, I consider biblical and theological representations of the physics of Spirit, including miracles, if also the politics of compassion, as related to bodies exhibiting disabilities. Christianity has shaped its understanding of divine power and, consequently, its social mission upon the dynamic trajectory it has read into miracle stories. And miracle stories, modern Christianity has assumed, obviously pivot upon the disabled body. I extend my range of concern to address how the modern template of normalcy and its contrary, degeneracy, have been deployed as maps of western Christianity's social mission. By concentrating on our reading of biblical theologies, especially our reading of Jesus as one with the monolithic power of Spirit to heal the blind, the cripple, the outcast, I attempt to deconstruct theology's psychic cathection to normalcy. I consider whether particular colonizing optics are still at work in today's most popular Christological proposals, the so-called "historical Jesus" portraits of Marcus Borg (1987) and John Dominic Crossan (1992). The essay concludes by suggesting another way of reading the miracle texts so as to disturb the optics of modern realism, especially their social effects